MULTICRITERIA DECISION AID FOR EVALUATION SUPPLIERS IN THE MANAGEMENT OF FOODSERVICE - Calazans, Dinara Leslye Macedo e Silva; Rocha, Fabrícia Abrantes Figueiredo da; Araújo, Afrânio Galdino de; Ferreira, Luciano (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The importance and complexity of the supplier selection problem have encouraged organizations to look for tools and techniques to improve this logistic process. The goal of this paper is present a model based on multicriteria decision theory to support managers from the collective feeding area to assess the performance of food suppliers, given its economic and social importance in Brazil. Our model was designed and validated in the context of foodservice, by using the multicriteria method ELECTRE II. We conducted a case study where the set of criteria, weights and alternatives were identified from decision-makers and specialized literature. The results obtained with the analysis of the existing suppliers allow decision-makers to propose different relationship strategies, corrective actions, and continuous improvement.